(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
In the formation of mathematical concepts in preschool children, it is directly related to the formation of elementary mathematical concepts in children and their preparation for school, the successful mastering of mathematical concepts by children, and the development of their perception, i.e. sensory feelings. How clear and solid mathematical concepts are, ensures the strength of children’s thinking, the processes of analysis and synthesis, logical thinking, and drawing conclusions. As a result of mathematical concepts, along with learning general knowledge, children develop such qualities as self-confidence, independent thinking, and the ability to express their thoughts beautifully.